Human DNA contamination of postmortem examination facilities: Impact of COVID‐19 cleaning procedure. Issue 5 (18th July 2022) - Bini, Carla; Giorgetti, Arianna; Giovannini, Elena; Pelletti, Guido; Fais, Paolo; Pelotti, Susi
Abstract: The DNA contamination of evidentiary trace samples, included those collected in the autopsy room, has significant detrimental consequences for forensic genetics investigation. After the COVID‐19 pandemic, methods to prevent environmental contamination in the autopsy room have been developed and intensified. This study aimed to evaluate the level of human DNA contamination of a postmortem examination facility before and after the introduction of COVID‐19‐related disinfection and cleaning procedures. Ninety‐one swabs were collected from the surfaces and the dissecting instruments, analyzed by real‐time quantitative PCR (q‐PCR) and typed for 21 autosomal STRs. Sixty‐seven out of 91 samples resulted in quantifiable human DNA, ranging from 1 pg/μl to 12.4 ng/μl, including all the samples collected before the implementation of COVID‐19 cleaning procedures ( n  = 38) and 29 out of 53 (54.7%) samples taken afterward. All samples containing human DNA were amplified, resulting in mixed (83.6%), single (13.4%), and incomplete (3%) profiles. A statistically significant decrease in DNA contamination was found for dissecting instruments after treatment with chlorhexidine and autoclave ( p  < 0.05). Environmental decontamination strategies adopted during COVID‐19 pandemic only partially solved the long‐standing issue of DNA contamination of postmortem examination facilities. The pandemic represents an opportunity to further stress the need for standardized evidence‐based protocols targeted to overcome the problem of DNA contamination in the autopsy room.